FORMAL ACTUALIZATION OF PRECEDENT TEXTS IN INTERTEXTUAL HEADINGS OF THE PRESS (Scientific journal of the Fergana State University, 2023)
The article is devoted to the problem of intertextuality as an active expressive means in the media language. The article aims to consider linguistic techniques of formal actualization of precedent texts in intertextual headings of the press. The main attention is focused on such transformations of the source text as word replacement, changing the grammatical meanings of words and the syntactic structure of the sentence, reduction.